2023
DOI: 10.3390/medicina59040746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Platelet-Rich Plasma Therapy in Oral Lichen Planus: A Systematic Review

Abstract: Background and Objectives: Oral lichen planus (OLP) is an autoimmune, mucocutaneous, oral potentially malignant disorder (OPMD), which characteristically manifests with chronic, recalcitrant lesions, with frequent flare-ups and remissions. The precise etiopathogenesis of OLP is still debatable, although it is believed to be a T-cell-mediated disorder of an unidentified antigen. Despite the availability of various treatments, no cure for OLP exists due to its recalcitrant nature and idiopathic etiology. Platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…The observed differences could be attributed to variations in the duration of release and peak time of GFs reported across studies [ 36 , 37 ].The UE Shinnawi study [ 38 ] also supports this notion, showing a clear improvement in symptoms with blood derivatives after the first two weeks of treatment. Several other studies have assessed the efficacy of injection PCs in managing refractory erosive OLP patients who showed no response to corticosteroid treatment [ 39 ]. The results revealed that PCs therapy is an effective approach for treating atrophic-erosive lesions associated with this condition, which is generally unresponsive to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences could be attributed to variations in the duration of release and peak time of GFs reported across studies [ 36 , 37 ].The UE Shinnawi study [ 38 ] also supports this notion, showing a clear improvement in symptoms with blood derivatives after the first two weeks of treatment. Several other studies have assessed the efficacy of injection PCs in managing refractory erosive OLP patients who showed no response to corticosteroid treatment [ 39 ]. The results revealed that PCs therapy is an effective approach for treating atrophic-erosive lesions associated with this condition, which is generally unresponsive to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) contains a platelet concentration five times higher than the baseline, cytokines, growth factors, adhesion molecules, a certain amount of red blood cells (RBCs) and white blood cells (WBCs) depending on the preparation method. It is obtained from fresh peripheral blood with a platelet concentration above the baseline value [51]. Platelet gel (PG) is derived from PRP and consists of platelet concentrate (PC) deposited in a semisolid network of polymerized fibrin.…”
Section: Platelet-rich Plasma and Platelet Gelmentioning
confidence: 99%
“…A high ratio between reactive oxygen species and intracellular antioxidants was related to inflammation in oral lichen planus. An in vitro study showed that VEGF within alphagranules activates nuclear factor (derived-erythrocyte) type 2 (Nrf2), which may prevent oxidative damage [93,94]. Additionally, the granules release anti-inflammatory cytokines such as IL-1 receptor antagonist (IL-1ra), soluble necrosis factor receptor (sTNF-R) I and II, IL-4, IL-10, IL-13, thereby providing anti-inflammatory effects in oral lichen planus [94][95][96].…”
Section: Oral Lichen Planusmentioning
confidence: 99%